2018
DOI: 10.1002/adfm.201802893
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Copper Window Electrodes with ≈108 Apertures cm−2 for Organic Photovoltaics

Abstract: A powerful approach to increasing the far-field transparency of copper film window electrodes which simultaneously reduces intraband absorption losses for wavelengths <550 nm and suppresses reflective losses for wavelengths >550 nm is reported. The approach is based on incorporation of a random array of ≈100 million circular apertures per cm 2 into an optically thin copper film, with a mean aperture diameter of ≈500 nm. A method for the fabrication of these electrodes is described that exploits a binary polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Many high performance OPVs use selective charge transport layers with conductivity substantially higher than that of MoO3-x, which enables their thickness to be increased so they can also serve as optical spacers [21] . The most widely used electron-selective layer is ZnO which is typically used with a thickness in the range 30-70 nm [22] . When deposited from a colloidal solution with low temperature annealing, as in this case, the conductivity of ZnO is at least an order of magnitude higher than evaporated MoO3-x, although is still very resistive [23] , as is evident from the current map in Figure 7a recorded using a c-AFM.…”
Section: High Performance Opvsmentioning
confidence: 99%
“…Many high performance OPVs use selective charge transport layers with conductivity substantially higher than that of MoO3-x, which enables their thickness to be increased so they can also serve as optical spacers [21] . The most widely used electron-selective layer is ZnO which is typically used with a thickness in the range 30-70 nm [22] . When deposited from a colloidal solution with low temperature annealing, as in this case, the conductivity of ZnO is at least an order of magnitude higher than evaporated MoO3-x, although is still very resistive [23] , as is evident from the current map in Figure 7a recorded using a c-AFM.…”
Section: High Performance Opvsmentioning
confidence: 99%
“…[11][12][13] It has also been shown that the higher optical losses in Cu, as compared to Ag, can be mitigated by electrode and/or device design, including using a metal oxide overlayer to increase transparency. [14][15][16] Due to the high surface energy of Cu and Ag these metals interact only weakly with glass and other technologically important transparent plastic substrates, such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), and so the formation of robust and continuous films of these metals with thickness < 10 nm is notoriously difficult to achieve using thermal evaporation. [3,17] Metal atoms condensing on the substrate diffuse over the surface and aggregate into particles which only form a continuous network for nominal thicknesses > 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years copper (Cu) has received growing attention as a low cost alternative to Ag for window electrode applications because it has an electrical conductivity comparable to Ag at ∼1% of the cost . It has also been shown that the higher optical losses in Cu, as compared to Ag, can be mitigated by electrode and/or device design, including using a metal oxide overlayer to increase transparency …”
Section: Introductionmentioning
confidence: 99%
“…Attractive alternatives to conventional TCOs are represented by metallic nanostructures in the form of ultrathin films (Stec et al, 2011;Zhang et al, 2017;Pereira et al, 2018) or multilayered structural configurations, such as dielectric/metal/dielectric (D/M/D), organic/metal/organic and polymer/metal/polymer architectures (Cattin et al, 2013;Della Gaspera et al, 2015;Guo et al, 2015;Aleksandrova et al, 2016;Kao et al, 2018;Liang et al, 2018). D/M/D are excellent candidates as transparent conductors (Bi et al, 2019): in general stacks based on Ag ultrathin films show the best optoelectrical properties (T = 80-90%, R s = 10-20 /sq) (Guo et al, 2012;Wang et al, 2014;Behrendt et al, 2015), but multilayers based on Au should be preferred for application in PSCs, due to their higher stability.…”
Section: Introductionmentioning
confidence: 99%